2017
DOI: 10.22159/ijap.2017v9i3.7056
|View full text |Cite
|
Sign up to set email alerts
|

Development and Physical Characterization of a Periodontal Bioadhesive Gel of Gatifloxacin

Abstract: Objective: The aim of this study was to develop a bioadhesive gel of gatifloxacin for the treatment of periodontal diseases.Methods: Periodontal gels of gatifloxacin were prepared using different hydrophilic polymers such as carbopol 940 (CP 940), carboxymethyl cellulose (CMC) and hydroxypropylmethyl cellulose (HPMC) in varied concentrations, either alone or as a combination. The prepared gels were evaluated for their physical appearance, pH, drug content, viscosity, bioadhesiveness and in vitro drug release p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
0
10
0
2
Order By: Relevance
“…The prepared formulations were colourless, viscous with no any aggregations and grittiness [14]. The physiological range of the nasal mucosa temperature lies between 32 and 35°C [15].…”
Section: Discussionmentioning
confidence: 95%
“…The prepared formulations were colourless, viscous with no any aggregations and grittiness [14]. The physiological range of the nasal mucosa temperature lies between 32 and 35°C [15].…”
Section: Discussionmentioning
confidence: 95%
“…In the study conducted by Kassab et al, in 2017, a biphasic release profile was reported for gatifloxacin from periodontal bioadhesive gel. The authors attributed the initial burst effect to the drug which is present freely in the gel matrix [48].…”
Section: In Vitro Drug Releasementioning
confidence: 99%
“…The dissolution medium phosphate buffer pH 7.4 was maintained at 37±5℃. The suitable volume of the sample was withdrawn at predetermined time periods; the same was replenished with fresh buffer and samples were assayed spectrophotometrically [8].…”
Section: In Vitro Release Studiesmentioning
confidence: 99%